PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY ( TSTS ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 019 SEKELADI ROKAN HILIR - Ruspidawati, Ruspidawati; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstact: The research aims to find out whether the implementation of two stay two stray (TSTS) method can improve social sciense learning results of class III student in SD Negeri 019 Sekeladi. The type of this research is classroom action research (CAR) with the research subjects are class III students which amounts to 16 students. The data collection techniques used is observation and tests. The research concluded that social sciense learning which using two stay two stray (TSTS) method can improve the teacherâs activity, studentâs activity and social science learning result. At the first meeting of cycle I, the teacherâs activity percentage was 62,5% and categorized enouhg, at the second meeting the percentage increased to be 71,87% and categorized good. For cycle II at the first meeting the percentage was 81,25% and categorized very good, at the second meeting increased to be 84,37% and categorized very good. Then for studentâs activity cycle I at the first meeting the percentage was 62,5% and categorized good, in the second meeting the percentage was 68,75% and categorized good. For the first meeting of cycle II the percentage was 78,12% and categorized good, at the second meeting the percentage was 87,5 and categorized very good. The studentâs social science learning result from the average grades before action (basic score) was 62,5 increased at cycle I to be 72,50 with the percentage increase by 16,0% and at cycle II the average grades increased to be 82,18 with the percentage increase by 31,5% from the basic score by 62,5.Keywords: Cooperative Type TSTS, learning result